Transition to Practice : a Toolkit for Newly Qualified Occupational Therapists. - Weyden, Ruth van der (Jessica Kingsley Publishers, 2018)
This is the occupational therapist's essential guide to transitioning smoothly to practice, including models and advice for working in diverse contexts, from adult social care to paediatric health care. It is full of helpful tips for coping with the organisational and emotional challenges of the job, and securing positive relationships for success.